2017
DOI: 10.1103/physreva.95.043426
|View full text |Cite
|
Sign up to set email alerts
|

Control of photoemission delay in resonant two-photon transitions

Abstract: The photoelectron emission time delay τ associated with one-photon absorption, which coincides with half the Wigner delay τ W experienced by an electron scattered off the ionic potential, is a fundamental descriptor of the photoelectric effect. Although it is hard to access directly from experiment, it is possible to infer it from the time delay of two-photon transitions, τ (2) , measured with attosecond pump-probe schemes, provided that the contribution of the probe stage can be factored out. In the absence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 23 publications
2
21
0
Order By: Relevance
“…Our measurement demonstrates that in the vicinity of a resonance, the f/b symmetry can also be broken during the continuum-continuum transitions. This finding is in agreement with a recent theoretical investigation of photoelectron interferometry, which demonstrated that the simple separation of the measured delay (t), in a sum of the contributions from Wigner (t W ) and continuumcontinuum (t cc ) delays, no longer held in the presence of a resonance (42). Argenti et al demonstrated that t W and t cc are entangled in resonant photoionization.…”
Section: Resonant Photoionizationsupporting
confidence: 90%
See 1 more Smart Citation
“…Our measurement demonstrates that in the vicinity of a resonance, the f/b symmetry can also be broken during the continuum-continuum transitions. This finding is in agreement with a recent theoretical investigation of photoelectron interferometry, which demonstrated that the simple separation of the measured delay (t), in a sum of the contributions from Wigner (t W ) and continuumcontinuum (t cc ) delays, no longer held in the presence of a resonance (42). Argenti et al demonstrated that t W and t cc are entangled in resonant photoionization.…”
Section: Resonant Photoionizationsupporting
confidence: 90%
“…However, their relative yield is strongly f/b asymmetric. This means that in the vicinity of resonances, where t W and t cc are entangled (42), the perturbative IR pulse can be used to break the f/b symmetry and to subsequently tailor asymmetric electronic wave packets, both in time and space. At larger emission angles, where the dynamics are governed by a single nonresonant pathway, the single-peak wave packets become f/b symmetric.…”
Section: Asymmetric Electron Wave Packetsmentioning
confidence: 99%
“…Hence, the streaking measurement probes the (long range) potential of the parent ion over a finite range only. While we focus here on interpretation and applications related to streaking time delays in one-photon ionization, we may note that recently the extension of the streaking concept to two-photon ionization within the present approach [11,12] as well as in other context [13][14][15][16] has been considered.…”
Section: Introductionmentioning
confidence: 99%
“…The phase shift φ 2n incorporates both the relative phase of two consecutive harmonics and the additional phase imparted to the photoelectron by the two-photon transition itself. In the special case in which one of the two harmonics excites a metastable state |a , therefore, the other harmonic can serve as a holographic reference to measure the phase of the resonant two-photon transition [3,[12][13][14]16]. Indeed, the phase shift in the sideband beating exhibits the rapid excursion characteristic of resonant amplitudes as a function of the detuning of the first harmonic from the intermediate resonance.…”
Section: Introductionmentioning
confidence: 99%